Wayang Wahyu sebagai Media Evangelisasi dalam Budaya Jawa - Fantaw, Jemmy (Perspektif, 2014)
Every local Church has her own way of expressing her faith, both in celebrating it within the Christian community and in doing mission outreach within the society at large. It is exactly what it means to be authentic. Being authentic is one of main concerns in the Christian communities of the Javanese cultural context. This article describes the way the Javanese Christian communities expressing and celebrating their faith, using their local genius, particularly in the case of wayang wahyu (biblical puppets). Traditionally wayang is performed not just for social and cultural entertainment but mostly for moral and spiritual education and guidance. Within this traditional style the puppet masters or puppeteers adopt biblical figures and narratives and Christian theology for the performance. Wayang wahyu could be regarded as a missiological breakthrough, since it is an alternative way of doing mission evangelization and catechism for Christians, which is also quite acceptable among the public and non-Christians who enjoy cultural performances. This article argues that wayang wahyu is not designed as a new paradigm of inculturation, but rather it is primarily an alternative way of doing mission evangelization, catechisis, and making the Christian faith closer to the people of the Javanese taste and background. Honestly, wayang wahyu is also another way to preserve the Javanese culture and promote its richness in this globalized era of high technology and advanced communications. For the Javanese, wayang is not only an art, it is precisely their identity.